The bioengineered prosthetic breast reconstruction: advancements, evidence, and outcomes - Nahabedian, Maurice Y. (Gland Surg, 2019)
Recent advancements in prosthetic breast reconstruction have provided the foundation for the bioengineered breast. These advancements include improved mastectomy techniques, autologous fat grafting, acellular dermal matrices (ADMs), and improved devices. Device-based breast reconstruction has evolved from subcutaneous, partial or total subpectoral, and now to prepectoral placement of devices. The evidence demonstrating the safety and efficacy of the bioengineered breast continues to increase. This manuscript will review the fundamental components of the bioengineered breast and provide an update of the current evidence.